Tension lap splices in UHPC beams: Influence of rebar size, steel fibers, splice length, and coarse aggregate. (1st September 2022) - Hung, Chung-Chan; Yuen, Terry YP.; Huang, Chih-Wei; Yen, Cheng-Hao
Abstract: Ultra-high performance concrete (UHPC) is a special type of fiber-reinforced cementitious composites and has been considered an effective solution to reduce the required development length for steel reinforcing bars due to its high bond strength. This study thoroughly investigated the bond strength of deformed steel bars in UHPC using four-point loading tests on sixteen large-scale lap splice UHPC beams. The experimental variables included the bar diameter, macro-steel fibers, splice length, and coarse aggregate. The splice strength of reinforcing bars was estimated using the proposed analytical model and strain gauge measurements. The results showed that the effects of spacing and sizes of reinforcing bars on the splice strength were obvious. The inclusion of coarse aggregate considerably enhanced the splice strength of reinforcing bars in UHPC. The fracture toughening effects by fibers and coarse aggregate can enhance the strain field uniformity in the lap spice zone and increase the bond strength. In addition to the experimental study, the applicability of several prevailing bond strength models for examining the splice strength of reinforcing bars in UHPC was evaluated. Based on the evaluation results, a suitable model that was able to predict the splice strengths of the tested beams with reasonable accuracy was suggested. Highlights: Small bar diameters adversely impacted the influence of fibers on splice strength. The inclusion of coarse aggregate in UHPC enhanced the splice strength. A suitable model that could reasonable predict splice strength was suggested. The size-effect of steel bars reduced the average splice strength. Inclusion of fibers enhanced splice strength for #11(D36) bars by up to 53%.